Challenges and possible solutions to creating an achievable and effective Post-2020 Global Biodiversity Framework - Alice Hughes; Xiaoli Shen; Richard Corlett; Lin Li; Maofang Luo; Stephen Woodley; Yuanming Zhang; Keping Ma (Ecosystem Health and Sustainability, 2022)
Global biodiversity is in crisis as a result of human activity. This biodiversity crisis has been well documented by scientists, recognized by world leaders, politicians, businesses, and citizens. Both the biodiversity and climate crises need to be addressed now. 2020 was when this change was supposed to start, with the 15th Conference of Parties (COP15) of the Convention on Biodiversity (CBD) meeting in Kunming, and the 26th Conference of Parties (COP26) of the UN Framework Convention on Climate Change meeting in Glasgow, but both meetings were postponed. COP26 was held a year late (November 2021), while COP15 was split into two, with the first part held in Kunming in October 2021, and the second part scheduled for Montreal in December 2022. This meeting in Montreal – arguably the most important in the CBDs history – must agree on the Post-2020 Global Biodiversity Framework (GBF), to reverse biodiversity loss. Failure to reach agreement in Montreal would ultimately be a failure of us all, with irreversible consequences for life on earth. Yet, with three months before the final deadline only 20% of text and two targets are agreed. This paper reviews the factors hindering progress on the agreement and suggests possible solutions.